Poly(ADP-ribosyl)ation of heterogeneous nuclear ribonucleoproteins modulates splicing. - Ji, Y.; Tulin, A.V. (Nucleic Acids Research, 2009)
The biological functions of poly(ADP-ribosyl)ation of heterogeneous nuclear ribonucleoproteins (hnRNPs) are not well understood. However, it is known that hnRNPs are involved in the regulation of alternative splicing for many genes, including the Ddc gene in Drosophila. Therefore, we first confirmed that poly(ADP-ribose) (pADPr) interacts with two Drosophila hnRNPs, Squid/hrp40 and Hrb98DE/hrp38, and that this function is regulated by Poly(ADP-ribose) Polymerase 1 (PARP1) and Poly(ADP-ribose) Glycohydrolase (PARG) in vivo. These findings then provided a basis for analyzing the role of pADPr binding to these two hnRNPs in terms of alternative splicing regulation. Our results showed that Parg null mutation does cause poly(ADP-ribosyl)ation of Squid and hrp38 protein, as well as their dissociation from active chromatin. Our data also indicated that pADPr binding to hnRNPs inhibits the RNA-binding ability of hnRNPs. Following that, we demonstrated that poly(ADP-ribosyl)ation of Squid and hrp38 proteins inhibits splicing of the intron in the Hsr omega-RC transcript, but enhances splicing of the intron in the Ddc pre-mRNA. Taken together, these findings suggest that poly(ADP-ribosyl)ation regulates the interaction between hnRNPs and RNA and thus modulates the splicing pathways.